China's Cybersecurity Governance As Part Of Foreign And Security Policy - Murniasari, Mira (Security Intelligence Terrorism Journal (SITJ), 2024)
Cyberspace has become a new method of interaction for humans in the digital industrial era. One of the countries that play an important role in global cyberspace is China, which has the largest number of internet users, reaching 989 million. This has prompted Chinese Government to formulate a complex cybersecurity governance strategy to maintain national stability and security. Therefore, this study aims to explore China's approach to cybersecurity at domestic and foreign levels. Domestic level explores the governance in the country by examining strategic documents, policies, as well as legal and institutional frameworks, while foreign level discusses cybersecurity as part of foreign and security policy. The primary focus of this study is the series of Chinese diplomatic initiatives aimed at shaping governance norms across various international forums.